PRESENTATION OF THE “AGING WELL” LAW - DIONISI-PEYRUSSE, Amélie (MEDECINE LEGALE DROIT MEDICAL, 2025)
The “ageing well” law has finally been adopted. It contains measures designed to strengthen the rights and autonomy of people who are vulnerable because of their age and/or disability. However, most of the amendments relating to the protection of adults have been withdrawn from the text.